(untitled) (Al-Qamar, 2025)
As global interconnectedness intensifies, the demand for learning Chinese as a foreign language continues to grow. In this context, Chinese language instruction must extend beyond linguistic competence to include the development of intercultural communication skills. This study explores three key areas: (1) Chinese language teachers’ perceptions of intercultural communication skills within the classroom; (2) the challenges encountered in fostering these skills among students; and (3) strategies for enhancing intercultural communication in the context of Chinese language teaching in Pakistan. Employing a qualitative research design, six Chinese language teachers were selected through purposive sampling. Data were collected via classroom observations and in-depth interviews, and analyzed using content analysis. Findings indicate that participants generally held positive attitudes toward intercultural communication skills and acknowledged their critical role in facilitating effective cross-cultural interaction. Nonetheless, several challenges emerged, including limited training, cultural misunderstandings, and lack of teaching resources. The study underscores the importance of ongoing professional development and institutional support to better equip teachers in integrating intercultural communication into their pedagogical practices.